Time-varying caloric vestibular stimulation for the treatment of neurodegenerative disease - Black, Robert D.; Chaparro, Eduardo (Frontiers in Aging Neuroscience, 2022)
Time-varying caloric vestibular stimulation (tvCVS) is a new form of non-invasive neurmodulation similar to, but different from, diagnostic CVS. Using a non-invasive, solid-state delivery device, tvCVS has been successfully used in a human clinical trial with Parkinson’s disease subjects. Additionally, the effects of tvCVS on brain activation have been studied in healthy human subjects using transcranial Doppler sonography (TCD) and functional magnetic resonance imaging (BOLD fMRI). A novel finding in the TCD and fMRI studies was the induction of cerebral blood flow velocity oscillations. How such oscillations might lead to the observed clinical effects seen in PD subjects will be discussed. Enabling studies of tvCVS with rodents is an attractive goal in support of explorations of the mechanism of action. Male Wistar rats were used in a proof-of-concept study described herein. Rats were anesthetized (isoflurane) and ventilated for the duration of the tvCVS runs. Time-varying thermal stimuli were administered using a digital temperature controller to modulate Peltier-type heater/cooler devices. Blunt ear bars conveyed the thermal stimulus to the external ear canals of the rats. Different thermal waveform combinations were evaluated for evidence of successful induction of the CVS effect. It was found that bilateral triangular thermal waveforms could induce oscillations in cerebral blood flow velocity (CBFv) both during and after the application of tvCVS. These oscillations were similar to, but different from those observed in awake human subjects. The establishment of a viable animal model for the study of tvCVS will augment ongoing clinical investigations of this new form of neuromodulation in patients with neurodegenerative disease.